Scope Squence Kurikulum - Mohamad Mustafid Hamdi (Intizam, Jurnal Manajemen Pendidikan Islam, 2018)
Education is the process by which people go through educational institutions (schools, colleges, or other institutions), which intentionally transforms their cultural heritage, namely knowledge, values ​​and skills from generation to generation. The more developed human civilization, the more developed the problems faced by education, thus increasingly demanding human progress in systematic thinking in education. Scope is the scope of the overall learning experience that will be given to students who have been in the form of a field of study, for example the field of science study for junior high (biology) which is detailed into the subject and sub-subject matter containing the scope of the material itself. To get clearer material can be obtained from books, textbooks or principal sources of the lesson. Squence means the arrangement or sequence of grouping activities or steps taken in curriculum planning. If the scope refers to "what", then the sequence refers more to "when" and "where" the points are placed and implemented. The compatibility of the lesson material depends on the objectives to be achieved, therefore in learning there must be curriculum development which includes Scope and Squence, so that the teaching and learning process in the school environment becomes better and achieves its educational goals.